Modeling the Structures of Oriented Macrofiber Polymer Composites as Capillary-Porous Bodies - Aleksandr E. Kolosov; Aleksandr V. Gondlyakh; Volodymyr I. Sivetskii; Elena P. Kolosova; Volodymyr V. Vanin; Dmytro E. Sidorov; Aleksandr L. Sokolskiy; Valeriy Yu Shcherbina; Igor I. Ivitskiy (Advances in Materials Science and Engineering)
The problems of modeling the structure and design of technical parameters for forming of oriented macrofiber polymer composites are analyzed. The considered approaches are based on the application of geometric modeling of the structure of oriented fibrous fillers and the design of the parameters of technical means for forming oriented macrofiber polymer composite materials. Peculiarities of the application of the phenomenological and structural approaches to the design of structural and technological parameters of technical means and to the calculation of the elements of composite structures based on oriented macrofibrous fillers are considered. The technique for determining the structural characteristics of oriented macrofibrillar fillers based on its adequate geometric model as capillary-porous bodies is given. As the structural characteristics, the porosity, the specific internal surface, and also the effective (hydraulic) capillary radius of oriented macrofibrous fillers are considered. It is noted that the obtained structural models are used, in particular, to the prognosis of the design and technological parameters of the technical means for molding macro-fiber polymer composite materials.